Saúde bucal de idosos longevos - Lewandowski, Andressa (2014)
INTRODUCTION: According to the Brazilian census of 2010, the elderly population has increased by 43.3%, while the population of the oldest old grew 72%. The literature is scarce regarding the oral health of the elderly and virtually no studies that address the oral health of elderly people 80 years and over in Brazil. Considering the high number of not only the elderly, but also the oldest old (80 years and older), this study aims to estimate the oral health status of the oldest old. METHODS: This is a quantitative, descriptive and analytical cross-sectional study. The sample consisted of 38 oldest old. We assessed self-perceived general and oral health and clinical oral conditions. RESULTS: Majority of them were women (71.1%), mean age of 89.1 years (±4.5). Participants reported having on average three morbidities (±2.3) and used an average of 3.9 medications (±2.8). The oldest old consider their oral health as poor (60.6%). They mostly used Denture, both in the upper arch (76.3%) and in the lower jaw (39.6%), and exhibit a high level of need for prostheses (81.6%). The mean DMFT (Decayed, Missing, Filled Teeth) was 29.2 with a component of teeth lost 84%. The oldest old have a significant demand for periodontal treatment. Vast majority of the oldest old in this study reported symptoms of xerostomia. CONCLUSION: The data obtained in this study show the marks left by time and lack of access and knowledge about oral care in this age group.